The role of trust as an electronic word of mouth mediation towards the interest in buying clothes online in Keenan Fashion in facebook application users - Arief Teguh Nugroho; Yuhaning Praborini; Ilma Maulina (Institute of Computer Science (IOCS), 2022)
The increasing number of online shopping transactions, especially through commerce, has given rise to a new phenomenon called live shopping. In this case, the seller will present a shopping atmosphere indirectly in front of the eyes of potential buyers. This study aims to 1) determine the effect of Ewom on consumer confidence when buying clothes online. 2) Knowing the effect of consumer trust on buying interest. 3) determine the effect of Ewom on buying interest. 4) Knowing Ewom influences the interest in buying clothes online through trust as a mediating variable. This study uses a quantitative approach involving 100 respondents. Collecting data using a questionnaire and using a literature study. Hypothesis testing in this study uses multiple linear regression analysis with a significance value of α = 5% using the SmartPLS 3.0 analysis tool. The results show that the electronic word of mouth variable has a significant effect on trust, trust has a significant effect on buying interest, Ewom has a significant effect on buying interest, as well as Ewom has a positive effect on buying interest through trust as a mediation.